Selecting a Discrete Multiple Criteria Decision Making Method to decide on a Corporate Relocation - Haddad, Malik; Sanders, David A; Tewksbury, Giles (Archives of Business Research, 2019)
This paper considers a corporate relocation problem. The research considered an approach to decide on an appropriate Multi-Criteria Decision Making (MCDM) method out of a subdivision of possible methods to rank five cities in the United States of America based on their suitability. Selecting the location of corporate real estate is key to optimizing an organization’s success.  The new approach provides decision makers with a recommended group of potentially suitable methods.  Sensitivity analysis is employed to explore the recommended group and to rate the robustness of their outputs when uncertainty and risk may be present.  A suitable method is recommended that provides a robust solution.  MCDM methods that can deal with a discrete set of alternatives were considered.  A MCDM method was recommended based on a best compromise in the minimum percentage change required in both the evaluation criteria and performance scores of the cities with respect to the evaluation criteria to alter the ranking of the cities.